Magnetohydrodynamic Flow of Viscous Fluid in a Slot Between Curvilinear Surfaces of Revolution - Sawicki, J. (Engineering Transactions, 1996)
This paper contains the study of the magnetohydrodynamic, steady, laminar flow of viscous fluid in a slot between curvilinear surfaces of revolution having a common axis of symmetry. The boundary layer equations are expressed in terms of the intrinsic curvilinear coordinate system x, θ, γ. The method of perturbation is used to solve the boundary layer equations. As a result, the formulae for parameters of the flow, i.e. the velocity components Vx, Vθ, Vγ and pressure p are obtained.